Progress on the Regulation of Ruminant Milk Fat by Noncoding RNAs and ceRNAs - Lu, QinYue; Chen, Zhi; Ji, Dejun; Mao, Yongjiang; Jiang, Qianming; Yang, Zhangping; Loor, Juan J. (Frontiers in Genetics, 2021)
Milk fat metabolism is not only a key factor affecting the quality of fresh milk but also a major target trait for common ruminant breeding. The regulatory mechanism of milk fat metabolism involves the expression of multiple genes, network regulation and signal transduction. To explore the principles of milk fat formation and its regulatory theory and pathway, this paper summarizes the existing literature data, discusses functional noncoding RNAs, and elaborates the epigenetic regulation of milk fat metabolism in ruminants. The results showed that microRNAs play key roles in the regulation of milk fat synthesis and catabolism in ruminants, and there are relatively few studies on the mechanisms by which lncRNAs and circRNAs regulate milk fat metabolism in ruminants. Particularly, there are few studies that focus on the regulation of milk fat by lncRNAs and circRNAs that act on milk fat metabolism-related genes through indirect action with microRNAs or RNAs in the ceRNA network, which has a positive effect on the expression of genes. In summary, the understanding of miRNA, lncRNA, circRNA and ceRNA mechanisms in regulating milk fat metabolism in ruminants is not comprehensive. Most studies focus on the regulation of the function of target gene mRNA through functional noncoding RNAs, although these regulatory mechanisms remain unclear. Few efforts have been directed to identify the factors that can regulate their own expression and function or to determine whether self-regulation involves positive and/or negative feedback. Moreover, many research results are not translatable for practical application. However, the study of functional noncoding RNA in milk fat metabolism in ruminants is increasing, and the results have shown significant application potential to provide new ideas for the study of milk fat regulation mechanisms in ruminants.